2008
DOI: 10.1111/j.1365-2362.2008.02063.x
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of cirrhosis of the liver has an impact on survival predicted by the Model of End‐stage Liver Disease score

Abstract: Our study suggests that aetiology of cirrhosis has an impact on 1-year survival predicted by the MELD score. This becomes more apparent in patients with advanced stage of liver disease (MELD >or= 16). Since MELD score is used for ranking patients for liver transplantation and waiting times are regularly longer than 3 months, our observations suggest that with increasing time on the waiting list and severity of disease, patients with viral cirrhosis may have a disadvantage in the current allocation policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…A liver transplant to an alcoholic, for example, is assumed to have lower success rates than to non-alcoholics, and the concern for high recidivism rates is explained as a reason for lower priority to alcoholics. Empirical evidence indicates, however, that transplants to victims of alcoholic cirrhosis may have better prognosis than victims of viral cirrhosis, and that relapse rate after transplantation is quite low 13 14…”
Section: Discussionmentioning
confidence: 99%
“…A liver transplant to an alcoholic, for example, is assumed to have lower success rates than to non-alcoholics, and the concern for high recidivism rates is explained as a reason for lower priority to alcoholics. Empirical evidence indicates, however, that transplants to victims of alcoholic cirrhosis may have better prognosis than victims of viral cirrhosis, and that relapse rate after transplantation is quite low 13 14…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the alcoholic etiology of liver disease, it is worth noticing that some authors have raised the question of cirrhotic patients due to alcoholism having a better outcome without transplantation than cirrhotics due to viral hepatitis (2) , and others have found that alcoholic patients had more post-transplant complications (30) . Both these remarks could reinforce that the reported trend in listing and transplanting less alcoholic patients might be positive to the system as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Angermayr et al found that the prediction of survival beyond three months in patients with viral cirrhosis and MELD P16 is not precisely assessed [65]. Moreover, Lucey et al demonstrated that MELD is a stronger predictor of waitlist mortality in non-alcoholic than alcoholic patients [66].…”
Section: Other Potential Pitfallsmentioning
confidence: 97%